2021
DOI: 10.3390/s21020601
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Human Center of Mass Position through the Inertial Sensors-Based Methods in Postural Tasks: An Accuracy Evaluation

Abstract: The estimation of the body’s center of mass (CoM) trajectory is typically obtained using force platforms, or optoelectronic systems (OS), bounding the assessment inside a laboratory setting. The use of magneto-inertial measurement units (MIMUs) allows for more ecological evaluations, and previous studies proposed methods based on either a single sensor or a sensors’ network. In this study, we compared the accuracy of two methods based on MIMUs. Body CoM was estimated during six postural tasks performed by 15 h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 54 publications
(84 reference statements)
0
3
0
Order By: Relevance
“…COP sway will be recorded using a force platform. Acceleration and angular velocity data gathered from the IMU placed on the lower back will be processed to estimate pelvis motion during the standing trial and quantify participants’ balance control performance [ 33 , 34 ]. Pelvis kinematics will also be evaluated through the motion capture system.…”
Section: Methodsmentioning
confidence: 99%
“…COP sway will be recorded using a force platform. Acceleration and angular velocity data gathered from the IMU placed on the lower back will be processed to estimate pelvis motion during the standing trial and quantify participants’ balance control performance [ 33 , 34 ]. Pelvis kinematics will also be evaluated through the motion capture system.…”
Section: Methodsmentioning
confidence: 99%
“…As described in the introduction, we used a multiple IMU-system because previous studies showed that it more accurately estimates the body's CoM [13]. However, the results of this work indicate that the plantar pressure system (Insoles) was still more reliable.…”
Section: A Influence Of Sensor Systemsmentioning
confidence: 95%
“…However this might lead to a feedback in a situation in which the posture itself is stable, such as during postural transitions. Thus, we decided to use a multiple IMU system, which can more accurately estimate CoM [13]. Moreover, in dynamic situations a beneficial effect of biofeedback has only be observed when force/pressure sensors have been used [4].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we will further study the relationship between action recognition analysis and objective posture evaluation. In the field of sports and technology, we will explore the use of complex and accurate sensing equipment to visualize technical actions in the field of sports and technology to solve the problem of pain points in data analysis in the field of physical training [31][32][33][34][35][36] .…”
Section: Usage Notesmentioning
confidence: 99%